Association Between Sociodemographic Characteristics and Assisted Childbirth by Qualified Personnel in Madagascar - Hery Sylvestre Bemanana (Journal of Family and Reproductive Health)
Objective: This study aims to analyze the association between the likelihood of giving birth in a healthcare facility and various sociodemographic characteristics in Madagascar. Materials and methods: This study utilized data from the 2021 Madagascar Demographic and Health Survey which included a representative sample of women of reproductive age (15-49 years). The sociodemographic variables analyzed included age, birth order, education level, region residence and economic status with the place of delivery being the primary dependent variable. Data analysis was conducted using R software. A chi-square test was applied to assess associations between variables, with a significance threshold set at 5%. Results: The prevalence of institutional childbirth services usage in Madagascar was 37.4% (35.1-39.7). The results showed that women under 20 years had an assistance rate of 36.7% (33.9-39.4), while the rate for primiparas reached 49.9% (48.5-51.3). Prenatal visits, mother’s age, birth order, region, residence, education level, and economic quintile significantly influenced access to care, with p-values < 0.0001. Only 17.5% (15.6-19.4) of women in the lowest quintile received qualified assistance at childbirth. Conclusion: The results highlight the impact of age, birth order, residence, education level, region and socioeconomic status on access to childbirth services, necessitating a multisectoral approach to improve equity.